Assessing the relation between waste management policies and circular economy goals. (December 2022) - D'Adamo, Idiano; Mazzanti, Massimiliano; Morone, Piergiuseppe; Rosa, Paolo
Highlights: End of waste policies can support the diffusion of WEEE and ELV practices. Social change is the most relevant issue to improve the correct disposal of MSWs. Behavioural and regulatory policies accelerate the transition towards circularity. Technological maturity seems to be already achieved. Rethinking needed is the scenario that best fit the waste management. Abstract: The European Union has recently prioritized waste policies by embedding them in the new Horizon Europe work programme. Here, circular economy (CE) and digitalization are matching together in order to support all the industrial sectors in increasing their sustainability level. One of the main impacts expected from the EU is a better exploitation of wasted resources. However, waste streams are very different in terms of volumes, embedded materials and management policies. Considering only those waste streams with highest volumes, this study focuses on End-of-Life Vehicle (ELV), Municipal Solid Waste (MSW) and Waste from Electrical and Electronic Equipment (WEEE). Starting from some policy recommendations and analyses identified through a literature review and the support of the experts, a survey has been conducted to identify the most critical items for each waste stream. Results of the survey show that, on the one hand, end of waste strategies has the highest importance for WEEE and ELV categories. On the other hand, social change has the highest importance for MSW. Consequently, end of waste strategies and social change should be considered as enablers of reuse and recycling practices in their reference contexts. In order to counteract the significant socio-economic issues already caused by delays in taking clear decisions about climate change mitigation strategies, policymakers should focus on these policy implications urgently if even more imminent environmental catastrophes are to be avoided.